2021
DOI: 10.1016/j.csbj.2021.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous modulators of neurotrophin signaling: Landscape of the transient ATP-NGF interactions

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 75 publications
1
13
1
1
Order By: Relevance
“…Recently, a study has been reported describing a thorough structural/biophysical study to characterize the interaction of ATP with recombinant human NGF (rhNGF). This study describes the molecular determinants of the interactions between ATP and rhNGF and allows to unveil the previously unknown binding sites on the molecular surface and the ligand’s orientation [ 5 ]. According to Isothermal Titration Calorimetry (ITC) data, ATP binds rhNGF with a low affinity (mM range), as confirmed by Surface Plasmon Resonance (SPR) and Saturation Transfer Difference NMR (STD-NMR).…”
Section: Ngf and Molecules Carrying Phosphate Groupsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, a study has been reported describing a thorough structural/biophysical study to characterize the interaction of ATP with recombinant human NGF (rhNGF). This study describes the molecular determinants of the interactions between ATP and rhNGF and allows to unveil the previously unknown binding sites on the molecular surface and the ligand’s orientation [ 5 ]. According to Isothermal Titration Calorimetry (ITC) data, ATP binds rhNGF with a low affinity (mM range), as confirmed by Surface Plasmon Resonance (SPR) and Saturation Transfer Difference NMR (STD-NMR).…”
Section: Ngf and Molecules Carrying Phosphate Groupsmentioning
confidence: 99%
“…The functional role of the ATP-rhNGF interaction in the context of TrkA and p75 NTR receptors was studied by SPR. Also, the investigation of the functional role of divalent ions (Mg 2+ or Zn 2+ ) in conjunction with ATP allowed to conclude that the relative stoichiometry of ATP-ion-rhNGF is a key factor for the regulation of the binding effect [ 5 ]. The structural/computation study pinpoints ATP as a genuine endogenous modulator of NGF signaling in vivo, in health and disease conditions.…”
Section: Ngf and Molecules Carrying Phosphate Groupsmentioning
confidence: 99%
See 3 more Smart Citations